ACCEPTANCE OF E-REVERSE AUCTION USE: A TEST OF COMPETING MODELS - Calisir, Fethi; Altin Gumussoy, Cigdem (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
This study aims to understand factors affecting e-reverse auction usage in companies by comparing three models: Technology Acceptance Model (TAM), Theory of Planned Behavior (TPB) and the integrated model (integration of TAM and TPB). Using LISREL 8.54, data collected from 156 employees working in the procurement department of companies in 40 different countries were used to test the models. Results indicated that, TPB may be more appropriate than the TAM and integrated model for explaining behavioral intention to use e-reverse auction. Behavioral intention to use is explained- by only attitude towards use in TAM; by subjective norms, perceived behavioral control and attitude towards use in both TPB and the integrated model. The other result suggests that actual use of e-reverse auction is directly predicted by behavioral intention to use in all three models. This study concludes with the discussion of the findings and implications for practitioners.